(untitled) (Education in the 21st Century, 2023)
In Ukraine, when a multicultural educational space becomes a reality, the artistic and aesthetic education of students becomes extremely relevant, which can ensure the development of tolerance in children, which implies respect for the point of view of another, a friendly attitude and interest in another culture, and finding constructive compromises. Today it is necessary to overcome the alienation of children and youth from the cultural and historical heritage of their ethnic group. Artistic and aesthetic education of youth can become the basis of intercultural interaction and communication, preservation and development of national identity. Actual today for higher education is the formation of future technology teachers’ ability to transform the competencies formed during training into school practice. With this in mind, our publication focuses on the specifics of the practical training of future technology teachers as part of their professional competence during the study of the course “Decorative and Applied Art” of the theme “Artistic Leather Products”. We believe that the practical mastery of future technology teachers by various types of arts and crafts is the core of creating optimal conditions for their professional training, which will allow creative self-realization in professional pedagogical activity.